Children's Digital Space: Educating on Social Media Ethics and Safety from Elementary School as an Effort to Support the Sustainable Development Goals: Ruang Digital Anak: Edukasi Etika dan Keamanan Bermedia Sosial Sejak Sekolah Dasar sebagai Upaya Mendukung Tujuan Pembangunan Berkelanjutan - Ayu Almahera; Rika Yuliwulandari; Nadya Wijaya Kusuma; Muhammad Fauzan Mahdi Abyansyah; Shalahuddin Reyshahry Alfarisi Sumarto; Gibran Jaya Silalahi; Arjun Eka Prambudi Tana; Sayed Abbas Alemi (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The development of digital technology has made the internet and social media an integral part of the lives of elementary school children. This provides great opportunities for children to learn and express themselves, but at the same time presents various risks if not balanced with adequate digital literacy. This digital literacy education activity aims to instill an understanding of social media ethics and safety from an early age in elementary school students. The program was implemented through the